Transglutaminases - a review with special reference to microbial transglutaminase and its application in food processing - TZIKAS (Ζ. ΤΖΗΚΑΣ) Z.; AMBROSIADIS (Ι. ΑΜΒΡΟΣΙΑΔΗΣ) I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Some properties and applications of the transglutaminase (TG), with particular focus on TG derived from microorganisms (MTG), are described. TG catalyzes an acyltransfer reaction in which the γ-carboxyamide groups of pep tidebound glutamine residues are the acyl-donors. Most food proteins, such as legume globulins, wheat gluten and gliadin, egg yolk and egg white proteins, meat actins and myosins, gelatin, collagen, milk caseins, a-lactalbumin and /Mactoglobulin, could be crosslinked by TG. TG are present in an extremely broad spectrum of living organisms, such as humans, most advanced animals, birds, amphibians, fish, plants and microorganisms. Commercial TG has been merely obtained from animal tissues for decades. The limited supply and the complicated separation and purification procedure for obtaining tissue TG have resulted in an extremely high price of the enzyme, which hampers a wide application in food processing. MTG, mass-produced at low cost by fermentation, catalyses the cross-linking of most food proteins through the formation of c-(v-glutamyl) lysine bonds, in the same way as wellknown mammalian enzymes. However, MTG is quite unique from other mammalian TG, since it is totally independent of Ca + and has a relatively lower molecular weight. The results of many studies suggest that MTG has many potential applications in food processing. Food treated with MTG appeared to have an improved flavour, appearance and texture. In addition, this enzyme can increase shelf-life and reduce allergenicity of certain foods. Using additional components, such as sodium ceseinate, maltodextrine and starch, MTG can be customized for use in many other foods, even those with lower protein content. In this respect, MTG technology will be an essential tool for producing acceptable protein foods from non-animal proteins in the future.